T cell activation is determined by the number of presented antigens - Deeg, Janosch A.; Axmann, Markus; Matić, Jovana; Liapis, Anastasia; Depoil, David; Afrose, Jehan; Curado, Silvia; Dustin, Michael L.; Spatz, Joachim P. (Nano letters, 2013)
Antigen recognition is a key event during T cell activation. Here, we introduce nanopatterned antigen arrays that mimic the antigen presenting cell surface during T cell activation. The assessment of activation related events revealed the requirement of a minimal density of 90-140 stimulating major histocompatibility complex class II proteins (pMHC) molecules per μm2. We demonstrate that these substrates induce T cell responses in a pMHC dose-dependent manner and that the number of presented pMHCs dominates over local pMHC density.